Perlaksanaan Ujian HIV Ke Atas Bakal Pengantin Di Negeri Johor: Satu Kajian Dari Sudut Undang-Undang Dan Syariah - Azman Ab Rahman; Syed Salim Syed Shamsuddin; Mushaddad Hasbullah; Yasmin Hanani Mohd Safian (Universiti Sains Islam Malaysia, 2024)
This study attempts to shed light on the implementation of the mandatory pre-marital HIV (Human Immunodeficiency Virus) testing on Muslim individuals in Johor and its effectiveness. This study also tries to trace the implications and consequences of the test upon the harrnonisation of Muslim family institutions specifically and the society at large, as well as to unveil the views of Syarac and Law on this issue together with its elaborations. The study adopts two kinds of methods. Firstly, library research which focuses on the collection of data from books, reports, statutes, enactments and others, both on the Islamic perspective and Family Law. Secondly, field research which denotes data collection through interviews with related authorities, either from the government or non-governmental organizations (NGOs), besides collecting feed backs and views fiom the state Muftis. The research discovered that the HIV pre-marital testing is only a mandatory and compulsory requirement in Johor, other states are still in the stage of planning and discussing the matter. The study also found out that Islam does not forbid the implementation of such testing for the sake of public interest. However, this study observed that the test is only compulsory to Muslim couples who wish to marry in Johor, which is based on the fatwa or religious decree on the issue made by the Johor Religious Council, without any legal enforcement binding it. Hence, this research is believed to be able to provide solutions to problems concerning human rights as well as to clear all doubts on the view of Islam and Law towards the pre-marital HIV test. It is also hoped that this research will be a significant reference and guide to any states in Malaysia wishing to implement the same test too.